Exploring the Fear of Birth Scale in a mixed population of women of childbearing age—A Swedish pilot study. Issue 5 (October 2018) - Hildingsson, Ingegerd; Rubertsson, Christine; Karlström, Annika; Haines, Helen
Abstract: Aim: The aim of this pilot study was to explore the Fear of Birth Scale in a mixed sample of women of childbearing age, by investigating the levels of childbirth fear and the content of women's thoughts when completing the scale. Methods: A cross-sectional mixed method study of 179 women who completed a short questionnaire and a think aloud interview. Results: The mean score of the Fear of Birth Scale was 40.80 (SD 27.59) and 28.5% were classified as having fear of childbirth (≥60). The internal consistency showed a Cronbach's α > 0.92, and a mean inter-item correlation of 0.85.The highest scores were found in women younger than 25 years (mean 60.10), foreign-born women (mean 54.30) and women who did not have any previous children (48.72). The lowest scores were found in women who had recently given birth (mean 34.82) and women older than 35 years (mean 34.85). The content analysis categorization matrix clearly accommodated all 436 statements into the five pre-existing categories. The largest categories were: the content of fear and worry with 138 statements and strategies to cope with fear or worry (122 statements). Conclusion: The Fear of Birth Scale seems to be a useful instrument for different subgroups of women. The construct of fear of childbirth may be universally understood and experienced by women of childbearing age irrespective of whether they are currently pregnant, have recently given birth or do not have children. Identifying fear of birth is important in clinical practice in order to support women's reproductive needs.